NEATH IV: an early onset of complex organic chemistry in molecular clouds - Priestley, Felix; Clark, P C; Ragan, S E; Scibelli, S; Cusack, M T; Glover, Simon; Fehér, O; Prole, L R; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2025)
Complex organic molecules (COMs) are widely detected in protostellar and protoplanetary systems, where they are thought to have been inherited in large part from earlier evolutionary phases. The chemistry of COMs in these earlier phases, namely starless and prestellar cores, remains poorly understood, as models often struggle to reproduce the observed gas-phase abundances of these species. We simulate the formation of a molecular cloud, and the cores within it, out of the diffuse interstellar medium, and follow the chemical evolution of the cloud material starting from purely atomic initial conditions. We find that the formation of both gas- and ice-phase COMs precedes the formation of cores as distinct objects, beginning at gas densities of a few 10 3 cm -3. Much of this COM-enriched material remains at these relatively modest densities for several Myr, which may provide a reservoir for accretion onto planet-forming discs in later evolutionary stages. We suggest that models of core and disc chemistry should not ignore the complex dynamical evolution which precedes these structures, even when studying supposedly late-forming molecules such as CH 3 OH and CH 3 CN.
Veröffentlicht: 31. Januar 2025
Gesehen am 06.10.2025